(untitled) (Nonconventional Technologies Review, 2015)
Flexible manufacturing widely used in the manufacturing industry, but the implementation o a flexible manufacturing system can raise a series of challenges regarding. An area where in the case of flexible manufacturing systems can generate problem and have a significant influence on the production cost is the management of the tool ware. Tool ware can have a significant influence on the cost efficiency of a flexible manufacturing system either trough the high cost of the tool or trough the problems caused the finished pieces during the production process by tools that are not in the specified parameters. The paper will present the main aspects of the tool ware and of the automatic tool rearrangement function, analyze the influence of the ATR in an FMS and present the general aspects of an ART function implementation at the University of Oradea.